COVID-19 vaccination-related tinnitus is associated with pre-vaccination metabolic disorders - Wang, Weihua; Yellamsetty, Anusha; Edmonds, Robert M.; Barcavage, Shaun R.; Bao, Shaowen (Frontiers in Pharmacology, 2024)
Cases of tinnitus have been reported following administration of COVID-19 vaccines. The aim of this study was to characterize COVID-19 vaccination-related tinnitus to assess whether there is a causal relationship, and to examine potential risk factors for COVID-19 vaccination-related tinnitus. We analyzed a survey on 398 cases of COVID-19 vaccination-related tinnitus, and 699839 COVID-19 vaccine-related reports in the Vaccine Adverse Effect Reporting System (VAERS) database that was retrieved on December 4, 2021. We found that following COVID-19 vaccination, 1) tinnitus report frequencies for Pfizer, Moderna and Janssen vaccines in VAERS are 47, 51 and 70 cases per million full vaccination; 2) the symptom onset was often rapid; 3) more women than men reported tinnitus and the sex difference increased with age; 4) for 2-dose vaccines, the frequency of tinnitus was higher following the first dose than the second dose; 5) for 2-dose vaccines, the chance of worsening tinnitus symptoms after second dose was approximate 50%; 6) tinnitus was correlated with other neurological and psychiatric symptoms; 7) pre-existing metabolic syndromes were correlated with the severity of the reported tinnitus. These findings suggest that COVID-19 vaccination increases the risk of tinnitus, and metabolic disorders are a risk factor for COVID-19 vaccination-related tinnitus.The study was approved by the University of Arizona Institute Review Board. A cross-sectional survey was conducted from August 12, 2021, to October 5, 2021, among the Facebook "Tinnitus and Hearing Loss/Impairment after COVID vaccination", a support group that was founded for sufferers of tinnitus and hearing loss post COVID-19 vaccination. The online survey was announced in the Facebook group, and the survey link was posted. Participation in the survey was voluntary. Participants were prescreened against inclusion criteria of vaccination status and the report of new or worsening tinnitus post COVID-19 vaccination. The participants provided consent by filling an online survey questionnaire that covered information on demography, general health before and after vaccination, noise exposure history, tinnitus assessment (Tinnitus Questionnaire, Tinnitus Functional Index and Visual Analogue Numeric Rating Scale), hearing evaluation (12-Question Short Form Speech, Spatial and Qualities of Hearing Scale) and attempted treatment of vaccination-related tinnitus (